REPORT ON HOLDING OF RUSSIAN NATIONAL CONGRESS OF CARDIOLOGY, OCTOBER 5-7, 2010 (Столичная издательская компания, 2016)
Report on holding of Russian National Congress of Cardiology, October 5-7, 2010.